Pre-drinking behaviour of people in the night-time economy: Evidence from a street-intercept survey in New Zealand - Cameron M; Miller P; Roskruge M (Wiley)
INTRODUCTION: Pre-drinking behaviour has grown in prevalence and generates harm for pre-drinkers and others. In this article, we answer three research questions: (i) Where and when do pre-drinkers obtain their alcohol?; (ii) What is the difference in the level of intoxication of pre-drinkers versus non-pre-drinkers, and how does this difference vary over the course of a night?; and (iii) Is the level of intoxication of pre-drinkers related to where and when they obtain their alcohol? METHODS: We obtained data from 469 respondents using a street-intercept survey conducted in Hamilton, New Zealand in 2019. Data were analysed by cross-tabulation, linear regression and plotting the average intoxication level in the night-time economy over time. RESULTS: The majority of pre-drinkers purchase their alcohol for pre-drinking on the day of consumption. Half of the same-day purchasers purchase before 6 pm. The average level of intoxication increases over the course of the night, and is unambiguously higher for pre-drinkers than non-pre-drinkers. The level of intoxication does not differ based on the source or timing of pre-drinking purchases. The main motivation for pre-drinking was price, especially among women. DISCUSSION AND CONCLUSIONS: Pre-drinking is a contributor to intoxication in the night-time economy, but most drinkers purchase their alcohol for pre-drinking before 7 pm. Further research is required to understand whether trading hours restrictions for off-premises alcohol suppliers will affect the most harmful drinking patterns. Price interventions to reduce the price differential between on-licenced and off-licence alcohol outlets offer the greatest potential to reduce pre-drinking and associated harm.
Keywords: pre-drinking; intoxication; night-time economy; New Zealand; 11 Medical and Health Sciences; 16 Studies in Human Society; 17 Psychology and Cognitive Sciences